Comparative Genomic Analysis of the Lettuce Bacterial Leaf Spot Pathogen, Xanthomonas hortorum pv. vitians, to Investigate Race Specificity - Rosenthal, Emma; Potnis, Neha; Bull, Carolee T. (Frontiers in Microbiology, 2022)
Bacterial leaf spot (BLS) of lettuce caused by Xanthomonas hortorum pv. vitians (Xhv) was first described over 100 years ago and remains a significant threat to lettuce cultivation today. This study investigated the genetic relatedness of the Xhv strains and the possible genetic sources of this race-specific pathogenicity. Whole genome sequences of eighteen Xhv strains representing the three races, along with eight related Xanthomonas strains, were included in the analysis. A maximum likelihood phylogeny based on concatenated whole genome SNPs confirmed previous results describing two major lineages of Xhv strains. Gene clusters encoding secretion systems, secondary metabolites, and bacteriocins were assessed to identify putative virulence factors that distinguish the Xhv races. Genome sequences were mined for effector genes, which have been shown to be involved in race specificity in other systems. Two effectors identified in this study, xopAQ and the novel variant xopAF2, were revealed as possible mediators of a gene-for-gene interaction between Xhv race 1 and 3 strains and wild lettuce Lactuca serriola ARM-09-161-10-1. Transposase sequence identified downstream of xopAF2 and prophage sequence found nearby within Xhv race 1 and 3 insertion sequences suggest that this gene may have been acquired through phage-mediated gene transfer. No other factors were identified from these analyses that distinguish the Xhv races.